PERAN END CHILD PROSTITUTION, CHILD PORNOGRAPHY AND TRAFFICKING OF CHILDREN FOR SEXUAL PURPOSES (ECPAT) INTERNASIONAL DALAM MENANGGULANGI KASUS CHILD TRAFFICKING DI ALBANIA (2007-2012) - Adni Luthfi Rafiqa; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research purpose to explain about the role of End Child Prostitution, Child Pornography and Trafficking of Children for Sexual Purposes (ECPAT) International to solve child trafficking case in Albania (2007-2012). ECPAT International is a non-governmental organization which take focus on solving child trafficking case and ECPAT International has had affiliate in some country in the world, one of them is Albania.Authors analyze and explain about child trafficking condition which is occured in Albania, like child prostitution, child pornography, child image abuse and child sex tourism. And Authors analyze how the role of a non-governmental organization, such as ECPAT International. This research use pluralism perspective by Diana L Eck, with group behavior analyzed level and the role of international organization theory by Clive Archer.This research shows that child trafficking condition which is occured in Albania have taken great portion on focus from ECPAT International until ECPAT International make the effort to do coalition with Albanian government to solve child trafficking case and also do coalition with some non-governmental organization which is focused to solve human trafficking case especially child trafficking.Keyword: child trafficking, role, ECPAT International, coalition, and non-governmental organization.